Digital Transformation of Librarians in Virtual Environment: Issues and Challenges - Sebastian, Rony (International Journal of Information Studies, 2025)
The latest developments in Information and Communication Technology (ICT) have made the concept â€œLibraries without wallsâ€ into a practical reality. This has posed several challenges to the information work force and the information users. Developments in computers, microelectronics and communication technologies have dramatically changed the library and information environment. In this regard, the information environment is changing greatly throughout the world. Digital libraries are emerging as an important area of research and number of other related disciplines for information science in information age. The facts generation has made a profound effect on availability and accessibility of e-assets. This research paper is highlighted infrastructure and generation as challenges dealing with and parameters of virtual environment. With the application of IT librarians could regularly triumph over such challenges and opportunities in consideration of customersâ€™ perspective. Librarians are facing different challenges which have been focused in this study.